3D Interfacial and Spatiotemporal Regulation of Human Neuroepithelial Organoids. Issue 22 (6th June 2022) - Tang, Chunling; Wang, Xinhui; D'Urso, Mirko; van der Putten, Cas; Kurniawan, Nicholas A.
Abstract: Neuroepithelial (NE) organoids with dorsal–ventral patterning provide a useful three‐dimensional (3D) in vitro model to interrogate neural tube formation during early development of the central nervous system. Understanding the fundamental processes behind the cellular self‐organization in NE organoids holds the key to the engineering of organoids with higher, more in vivo‐like complexity. However, little is known about the cellular regulation driving the NE development, especially in the presence of interfacial cues from the microenvironment. Here a simple 3D culture system that allows generation and manipulation of NE organoids from human‐induced pluripotent stem cells (hiPSCs), displaying developmental phases of hiPSC differentiation and self‐aggregation, first into NE cysts with lumen structure and then toward NE organoids with floor‐plate patterning, is established. Longitudinal inhibition reveals distinct and dynamic roles of actomyosin contractility and yes‐associated protein (YAP) signaling in governing these phases. By growing NE organoids on culture chips containing anisotropic surfaces or confining microniches, it is further demonstrated that interfacial cues can sensitively exert dimension‐dependent influence on luminal cyst and organoid morphology, successful floor‐plate patterning, as well as cytoskeletal regulation and YAP activity. This study therefore sheds new light on how organoid and tissue architecture can be steered through intracellular and extracellular means. Abstract : The formation of human cystic neuroepithelial (NE) organoids can be induced in a simple yet manipulatable 3D culture system. Single pluripotent stem cells undergo self‐aggregation and differentiation, lumen formation and polarization, and finally form floor‐plate patterned NE organoids. These developmental phases are shown to be sensitive to interfacial cues, providing a new avenue to modulate organoid formation and maturation.